TUMOR IN HORSESHOE KIDNEYS: A CASE REPORT AND LITERATURE REVIEW - Sutojo, Bobby; Bramono, Ikhlas Arief; Harahap, Edward Usfie; Santoso, Rachmat Budi; Treswari, Galuh Ayu; Putri, Rizky Ifandriani; Mahdi , Hardini Intan Setiawati (Indonesian Urological Association, 2024)
Objective: This study aims to report a renal tumor in a horseshoe kidney successfully treated with an open left nephrectomy. Case(s) Presentation: A 3 years old girl with a lump in the left abdomen and intermittent hematuria was referred to our hospital. Whole abdominal contrast CT scan showed the presence of a left renal mass in a horseshoe kidney that infiltrates the left renal artery and is attached to the spleen. The patient underwent preoperative chemotherapy followed by surgical resection. Discussion: In a horseshoe kidney, renal tumors are uncommon. The limited kidney mobilization and access to the renal hilum and the abnormal and highly variable vasculature make surgical treatment of a tumor in a horseshoe kidney extremely difficult. Conclusion: Open surgery continues to be the treatment of choice for horseshoe kidney tumors due to their anatomical complexity, particularly in cases where the tumor is difficult to eradicate. Keywords: Renal tumor, horseshoe kidney, surgical management.